In noise we trust? Optimal monetary policy with random targets - Ethan Cohen-Cole; Bogdan Cosmaciuc (Federal Reserve Bank of Boston, 2006)
We show that a monetary policy in which the central bank commits to a randomized inflation target allows for potentially faster-expectations convergence than with a fixed target. The randomized target achieves faster convergence in particular in transition environments: those demonstrating either particularly high or low inflation.
Keywords: E52; E61; E42; 330; Monetary policy; asymmetric information; Bayesian rational expectations; commitment